مواقف ابن قدامة تجاه آراء المعتزلة الأصولية من خلال كتاب روضة الناظر وجنة المناظر - Muhamad Subhi Apriantoro; Muhammad Muinudinillah Basri (Profetika: Jurnal Studi Islam, 2017)
This publication discusses the thought of ushul fiqh Mu’tazilah in the book of Raudhot an-Nadzir wa Jannat al-Manadzir written by Ibnu Qudamah. The book is the summary of Al Mustashfa written by Imam Al Ghozali. Al Mustasfha contains diction which is not easily understood. It relates with the method used by Imam Al Ghazali namely method of Al-Mutakallimin. Therefore, book of Raudhot an-Nadzir wa Jannat al-Manadzir discusses the thought of ushul fiqh Mu’tazilah. The method of the research was qualitative method. It can be identified that Ibnu Qudamah adopts the thought of Al Ghozali without putting down his name in his book. In this book, Ibnu Qudamah sometimes has the same and different opinion with Al Ghozali. However, they also have same thought with different sampling cases. The thought of ushul fiqh Mu’tazilah influences the method of contemporary ushul fiqh. One of the influences is a human freedom to do ijtihad with the right to create their own fate. There is also a difference between old and new Mu’tazilah.  In the old perspective, the law consideration is about God (theocentric). Meanwhile, in the new perspective, the law consideration is about human (anthropocentric) يبحث في هذه النشرة عن آراء المعتزلة الأصولية التي أوردتها ابن قدامة خلال كتابه روضة الناظر وجنة المناظر لما كان هذا الكتاب مختصرا من كتاب المستصفى في علم الأصول لأبي حامد الغزالي فقد عرض كثير من عبارته بغموض وإبهام. هذا لا يخرج عن كون الغزالي نهج منهج المتكلمين في كتابة المستصفى. لهذا قد تميز روضة الناظر بآراء المعتزلة الأصولية. سلك الباحث منهج كيفي تبين من البحث أن ابن قدامة مهما كان أخذ كثير من آراء الغزالي في كتابه، وهو لم يذكر اسم الغزالي قط خلال كتابه، وافق الغزالي تارة وخالفه تارة، أو وافقه في المعنى وخالفه في الأمثلة. وآراء المعتزلة الأصولية لها تأثير كبير في مناهج الأصولية المعاصرة، منها أن باب الاجتهاد فتح بشكل واسع للحرية الأفعال الإنسانية، وجود الفروق بين مبنى الفكرة المعتزلة القدماء بمن يدعى أنه المعتزلة بثوبها الجديد. أن المعتزلة القدماء يجعلون الإله محور كل شيء، أما المعتزلة المعاصرة فإنهم جعلوا الإنسان محور كل شيء.